Educational Setting and SARS-CoV-2 Transmission Among Children With Multisystem Inflammatory Syndrome: A French National Surveillance System - Guenver, Celia; Oualha, Mehdi; Levy, Corinne; Antona, Denise; Madhi, Fouad; Toubiana, Julie; Lachaume, Noémie; Javouhey, Etienne; Lorrot, Mathie; Yang, David Dawei; Levy, Michael; Caseris, Marion; et al. (Frontiers in Pediatrics, 2021)
Background: Multisystem inflammatory syndrome in children (MIS-C) is the most severe form associated with SARS-CoV-2 infection in children. To reduce the spread of SARS-CoV-2 at the population level, educational setting closure have been implemented in many countries. However, the direct benefit of school closure on the MIS-C burden remains to be explored. We aimed to assess the role of educational settings in SARS-CoV-2 transmission among children with MIS-C. Methods: We conducted a French national prospective surveillance of MIS-C, coordinated by Public Health France, from April 2020 to March 2021. During this period, we included all children with MIS-C fulfilling the WHO definition who were reported to Public Health France. For each child, we traced the source of SARS-CoV-2 transmission. The main outcome was the proportion of children with MIS-C, with educational setting-related SARS-CoV-2 infection, during the period of school opening. Results: We included 142 children fulfilling WHO criteria for MIS-C: 104 (70%) cases occurred during school opening periods. In total, 62/104 children (60%, 95%CI [50; 69]) had been contaminated by a household contact and 5/104 in educational settings (5%, 95%CI [2; 11]). Among children with MIS-C occurring during school closure periods, the proportion of household transmission remained similar (66%, 25/38). Conclusion: Children with MIS-C were mainly infected by SARS-CoV-2 within their family environment, and the educational setting played a marginal role in this transmission. This suggests that mitigating school attendance may not reduce substantially the burden of MIS-C.